Pengaruh Kualitas Produk Dan Kualitas Pelayanan Terhadap Kepuasan Pelanggan Mie Gacoan Di Cabang Gianyar - Kayama, I Gusti Ngurah Ary; Winata, I Made Budi Ari; Marzio, Komang Viar; Rahmayanti, Putu Laksmita Dewi (JURNAL MANAJEMEN DAN BISNIS, 2022)
Developments and changes during the current pandemic have an impact on changes in people's lifestyles and technological advances. The existence of this lifestyle is an opportunity for entrepreneurs to create new business initiatives, especially food and beverage companies, so that currently many food companies are growing, especially in the city of Gianyar. One of them is the food company Mie Gacoan Gianyar. Mie Gacoan is one of the retail businesses whose retail products are in the form of processed noodles, dim sum and beverages. Review Mie Gacoan is a registered trademark of the number one spicy noodle restaurant chain in Indonesia, a subsidiary of PT Pesta Pora Abadi. In running a business in the food and beverage sector, the Gacoan Noodle Company must examine various aspects ranging from customer satisfaction, service quality, and the quality of the products they sell in order to further develop the Gacoan noodle food and beverage business.